Recent Advances in Immunothrombosis and Thromboinflammation - Kaiser, Rainer; Gold, Christoph; Stark, Konstantin (Thrombosis and Haemostasis, 2025)
Inflammation and thrombosis are traditionally considered two separate entities of acute host responses to barrier breaks. While inciting inflammatory responses is a prerequisite to fighting invading pathogens and subsequent restoration of tissue homeostasis, thrombus formation is a crucial step of the hemostatic response to prevent blood loss following vascular injury. Though originally designed to protect the host, excessive induction of either inflammatory signaling or thrombus formation and their reciprocal activation contribute to a plethora of disorders, including cardiovascular, autoimmune, and malignant diseases. In this state-of-the-art review, we summarize recent insights into the intricate interplay of inflammation and thrombosis. We focus on the protective aspects of immunothrombosis as well as evidence of detrimental sequelae of thromboinflammation, specifically regarding recent studies that elucidate its pathophysiology beyond coronavirus disease 2019 (COVID-19). We introduce recently identified molecular aspects of key cellular players like neutrophils, monocytes, and platelets that contribute to both immunothrombosis and thromboinflammation. Further, we describe the underlying mechanisms of activation involving circulating plasma proteins and immune complexes. We then illustrate how these factors skew the inflammatory state toward detrimental thromboinflammation across cardiovascular as well as septic and autoimmune inflammatory diseases. Finally, we discuss how the advent of new technologies and the integration with clinical data have been used to investigate the mechanisms and signaling cascades underlying immunothrombosis and thromboinflammation. This review highlights open questions that will need to be addressed by the field to translate our mechanistic understanding into clinically meaningful therapeutic targeting.
Keywords: inflammation; thrombosis; platelets; neutrophils; megakaryocytes